Surveillance and Correlation of Antibiotic Prescription and Resistance of Gram-Negative Bacteria in Singaporean Hospitals - Hsu, Li-Yang (American Society for Microbiology (ASM), 2010)
A surveillance study was performed in four Singapore public hospitals from 2006 to 2008 to determine the correlation between antibiotic prescription and Gram-negative bacterial antimicrobial resistance. Targeted organisms included ceftriaxone- and ciprofloxacin-resistant Escherichia coli and Klebsiella pneumoniae, as well as imipenem-resistant Pseudomonas aeruginosa and Acinetobacter spp. Antibiotic prescription data were collated in the WHO anatomical therapeutic chemical (ATC)/defined daily dose (DDD) format, while antibiotic resistance was expressed as incidence density adjusted for total inpatient-days every quarter. Individual trends were determined by linear regression, while possible associations between antibiotic prescription and resistance were evaluated via cross-correlation analysis. Results over 3 years indicated significantly rising incidence densities of ceftriaxone- and ciprofloxacin-resistant E. coli and imipenem-resistant Acinetobacter spp. (blood isolates only). Antimicrobial-resistant Klebsiella pneumoniae rates declined. The prescription rates of piperacillin-tazobactam, ertapenem, meropenem, ciprofloxacin, and levofloxacin increased significantly, while imipenem and moxifloxacin prescription decreased. Cross-correlation analysis demonstrated possible associations between prescription of fluoroquinolones and ciprofloxacin-resistant E. coli (R(2) = 0.46), fluoroquinolones and ceftriaxone-resistant E. coli (R(2) = 0.47), and carbapenems and imipenem-resistant Acinetobacter spp. (R(2) = 0.48), all at zero time lag. Changes in meropenem prescription were associated with a similar trend in imipenem-resistant Acinetobacter blood isolates after a 3-month time lag. No correlation was found between cephalosporin use and resistance. In conclusion, our data demonstrated correlation between prescription of and Gram-negative bacterial resistance to several, but not all, key antimicrobial agents in Singapore hospitals. In areas where Gram-negative bacterial resistance is endemic and prescription of broad-spectrum antimicrobial agents is high, factors other than antimicrobial usage may be equally important in maintaining high resistance rates.